Effects of Color Modifier on Degree of Monomer Conversion, Biaxial Flexural Strength, Surface Microhardness, and Water Sorption/Solubility of Resin Composites - Pipop Saikaew (MDPI AG, 2021)
Color modifiers can be mixed with resin composites to mimic the shade of severely discolored tooth. The aim of this study was to assess the effects of a color modifier on the physical and mechanical properties of a resin composite. The composite was mixed with a color modifier at 0 wt% (group 1), 1 wt% (group 2), 2.5 wt% (group 3), or 5 wt% (group 4). The degree of monomer conversion (DC) was examined after light curing for 20 or 40 s. Biaxial flexural strength (BFS)/modulus (BFM), surface microhardness (SH), and water sorption (Wsp)/solubility (Wsl) were also tested. The DC of group 1 was significantly higher than that of groups 3 and 4. The increase in curing time from 20 to 40 s increased the DC by ~10%. The BFS, BFM, Wsp, and Wsl of all the groups were comparable. A negative correlation was detected between the concentration of color modifier and the BFS and DC, while a positive correlation was observed with Wsp. In conclusion, the color modifier reduced the DC of composites, but the conversion was improved by extending the curing time. The increase in color modifier concentration also correlated with a reduction in strength and the increase in the water sorption of the composites.